Analisa Menambah Surat Gugat dapat dilakukan Sepanjang tidak Merubah dan Menambah Kejadian Materiel Berdasarkan Pasal 127 RV (Perkara No. 79/Pdt.G/2020/PN JKT.SEL) - Agus Sugiono; Zaenal Arifin; Tubagus Ahmad Suhendar (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
Sri Bintang Pamungkas, as Plaintiff and Fahrizal Fardiansyah as Main Director of PT. Eora Mitra Sejati as Defendant. The Plaintiff prevented the auction process for the Wilis parcels by the Auction Center through BCA, which was borrowed incorrectly by the Defendant as Collateral to obtain a credit facility from BCA in the amount of Rp. 1,800,000,000,- which ended in default by exchanging Collateral from the Wilis parcels with the central Kalibata parcels. The plaintiff intends to obtain control over all assets of PT. Eora Mitra Sejati which is still left from the proceeds from receiving the BCA credit facility. On July 16, 2014, a Bank BCA credit agreement was held. Based on the credit agreement, BCA agreed to provide local credit facilities not exceeding Rp. 1,200,000,000.- to the Defendant (PT. Eora Mitra Sejati) Which facility will be used for the company's working capital, the length of the loan extension as of July 17 2014 ending July 17 2015 credit interest must be paid at 14.25% per year on loans made stated that it is paid every month, which credit interest can be reviewed, for the first time on May 9, 2019 by providing details of the amount of debt that must be repaid without notification to the Plaintiff and Mrs. Emalia. According to his statement, the Plaintiff has paid more than 5 years to BCA approximately 60 times each in the amount of Rp. 20,000,000, - which is considered as a loan interest payment, while the principal loan payment is only paid once, namely in November 2019 in the amount of Rp. 100,000,000, - then the Plaintiff and Mrs. Emalia on 23 December 2019 met the head of the BCA office in the Bidakara building and the Plaintiff added a payment of Rp. 70,000,000, - the plaintiff requested permission to change to the Panel of Judges to include certificate of ownership no. 03554/Mampang with an area of ​​2,114 m2 in the name of Defendant (now please call Defendant I) MA jurisprudence No. 547K/SIP/1973 states: changes to the lawsuit regarding the subject matter of the case are changes to the subject matter of the lawsuit. Therefore, it must be rejected. 03554 Mampang with an area of ​​2,114 m2 on behalf of the Defendant (now please call it Defendant I) considering that because the Plaintiff had crossed the tolerance limit in changing the lawsuit, the panel of judges considered that the plaintiff's lawsuit must be rejected.